Development of a new ultrasound scoring system to evaluate glandular inflammation in Sjögren's syndrome: an OMERACT reliability exercise. (25th November 2021) - Hočevar, Alojzija; Bruyn, George A; Terslev, Lene; De Agustin, Juan Jose; MacCarter, Daryl; Chrysidis, Stavros; Collado, Paz; Dejaco, Christian; Fana, Viktoria; Filippou, Georgios; Finzel, Stephanie; Gandjbakhch, Frederique; et al.
Abstract: Objective: The aim of this exercise from the OMERACT Ultrasound subgroup on Sjögren's syndrome was to develop and assess the reliability of a consensus-based semiquantitative colour Doppler US scoring system for pathologic salivary gland vascularization in patients with primary Sjögren's syndrome (pSS). Methods: Using the Delphi method, a colour Doppler semiquantitative scoring system for vascularization of bilateral parotid and submandibular glands was developed and tested in static images and on patients (9 pSS patients and 9 sonographers). Intra-reader and inter-reader reliability of grading the salivary glands were computed by weighted Cohen and Light's kappa analysis, respectively. Results: The consensus-based semiquantitative score was: grade 0, no visible vascular signals; grade 1, focal, dispersed vascular signals; grade 2, diffuse vascular signals detected in <50% of the gland; grade 3, diffuse vascular signals in >50% of the gland. In static images, the intra- and inter-reader reliability showed excellent kappa values (95% CI) of 0.90 (0.87, 0.93) and 0.80 (0.74, 0.84), respectively, for all four salivary glands together. In patients, the intra- and inter-reader reliability for all four salivary glands together was kappa = 0.84 (0.73, 0.92) and 0.70 (0.64, 0.76), respectively. Conclusion: The consensus-based colour Doppler US scoring for the evaluation of salivary gland vascularization in pSS showed a good inter-reader reliability and excellent intra-reader reliability in static images and in patients. The clinical application of the developed scoring system should be tested in clinical settings.